2007
DOI: 10.1111/j.1523-5378.2007.00511.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Postulated Mechanisms Concerning the Association of Helicobacter pylori with Ischemic Heart Disease

Abstract: Since its discovery, Helicobacter pylori has been implicated in the pathogenesis of several diseases, both digestive and extradigestive. Interestingly, the majority of the extradigestive-related literature is focused on two vascular manifestations: stroke and ischemic heart disease. Potential mechanisms for the establishment of a H. pylori-induced ischemic heart disease have been proposed with regard to chronic inflammation, molecular mimicry, oxidative modifications, endothelial dysfunction, direct effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 133 publications
0
36
0
1
Order By: Relevance
“…Helicobacter pylori infection is putatively associated with extra-digestive disorders [2][3][4][5][6][7][8] and may also play a role in the development of autoimmune diseases [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Helicobacter pylori infection is putatively associated with extra-digestive disorders [2][3][4][5][6][7][8] and may also play a role in the development of autoimmune diseases [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Helicobacter pylori, the major causal agent of several acute and chronic gastroduodenal disease, has been involved in various aspects of many extragastric manifestations, such as ischemic heart disease 3) . Kowalski et al elucidated that Helicobacter pylori DNA was significantly found in atherosclerotic plaques of patients with severe coronary artery disease and Helicobacter pylori infection could progress and destabilize coronary artery plaque in a direct manner 4) .…”
Section: On Lipid Profile and Helicobacter Pylori Infectionmentioning
confidence: 99%
“…Several possible pathogenetic models have been presented to explain the relationship between HP infection and atherosclerosis, including induction of an atherogenic modified lipid profile, systemic increase of inflammatory markers, establishment of a hypercoagulabile state, changes regarding homocysteine levels, direct effect of HP on the progression and instability of atherosclerotic plaques, and induction of platelet aggregation [18]. Especially intriguing is the autoimmune hypothesis of possible antigen mimicry between HP antigens and antigens within atherosclerotic plaque.…”
Section: Introductionmentioning
confidence: 97%